Comparison of the effectiveness of recombinant human growth hormone therapy in preterm and full-term children with short stature born small for gestational age - Dohyung Kim; Ji-Hee Yoon; Soojin Hwang; Ja Hye Kim; Han-Wook Yoo; Jin-Ho Choi (Annals of Pediatric Endocrinology & Metabolism, 2025)
Purpose With improvements in the infant survival rates for high-risk pregnancies, the prevalence of short stature in children born prematurely and small for gestational age (SGA) has also increased. The aim of this study was to compare the effectiveness of recombinant human growth hormone (rhGH) therapy for preterm and full-term SGA children with short stature. Methods This study included 114 children born SGA (40 preterm and 74 term), who showed no catch-up growth by age 4 years and had undergone rhGH therapy for at least one year. The clinical parameters were reviewed retrospectively. Results The mean height standard deviation scores (SDSs) for preterm and full-term SGA children at the start of rhGH therapy were -2.97±0.85 and -2.46±0.54, respectively. The mean duration of treatment was 3.3±1.9 years for preterm SGA children and 3.3±1.6 years for full-term SGA children. The height SDS increased to -1.13±0.96 in preterm children and -0.77±0.59 in full-term children by the fourth year of treatment. Full-term SGA children responded better to rhGH therapy than preterm children in the first year of therapy (P=0.03). Serum insulin-like growth factor 1 and insulin-like growth factor binding protein 3 levels significantly increased after the start of rhGH therapy (P<0.001). Conclusions rhGH therapy significantly improved height SDS in both preterm and full-term SGA children, emphasizing the key role of this intervention for managing short stature in children born SGA, regardless of gestational age.